Phase I/II trial of the combination of midostaurin (PKC412) and 5‐azacytidine for patients with acute myeloid leukemia and myelodysplastic syndrome. Issue 4 (2nd March 2015) - Strati, Paolo; Kantarjian, Hagop; Ravandi, Farhad; Nazha, Aziz; Borthakur, Gautam; Daver, Naval; Kadia, Tapan; Estrov, Zeev; Garcia‐Manero, Guillermo; Konopleva, Marina; Rajkhowa, Trivikram; Durand, Menda; et al.
Abstract : We investigated the combination of midostaurin and azacitidine (AZA) in patients with acute myeloid leukemia (AML) and high risk myelodysplastic syndrome (MDS). Patients received AZA 75 mg m −2 on days 1–7 and midostaurin 25 mg bid (in cohort 1 of phase I) or 50 mg bid (in cohort 2 of Phase I and in Phase II) orally on day 8–21 during the first cycle and continuously thereafter. Fourteen patients were enrolled in the phase I and 40 in the phase II. Overall response rate was 26%. The median remission duration (RD) was 20 weeks and was significantly longer in patients with FLT3 mutations not previously exposed to other FLT3 inhibitors ( P = 0.05) and in patients not previously transplanted ( P = 0.01). Thirty‐two (59%) patients have died, all of complications related to disease progression. G3‐4 nonhematological toxicity was reported in 38 (70%) patients, most frequently infections (56%), ejection fraction reduction (11%), and diarrhea or nausea/vomiting (9% each). The combination of midostaurin and AZA is an effective and safe regimen in patients with AML and high‐risk MDS. Patients with FLT3 mutations but not previously exposed to other FLT3 inhibitors and patients not previously transplanted derived the greatest benefit. Further studies with this combination are warranted. Am. J. Hematol. 90:276–281, 2015. © 2014 Wiley Periodicals, Inc.